(untitled) (Psychology Travelogs, 2024)
The article considers the definition of the concepts of fabbing, doomscrolling, nomophobia and analyzes the causes of occurrence, characteristic signs of human behavior. It has been established that phabing is a phenomenon when a person ignores direct interpersonal communication due to the obsessive use of a smartphone or other gadgets, being distracted by them while communicating with partners, relatives or relatives. The main reasons for fabbing are excessive dependence on mobile devices, the desire to get instant gratification from social networks and the search for new information. Doomscrolling is an internal psychological/mental discomfort manifested by endless scrolling of news and social media and prolonged reading of negative information against the background of negative events and leads to disruption of the individual’s vital activities. Reasons for this phenomenon include information overload, anxiety over global events, and a desire to keep up with the latest news. Nomophobia is an anxiety disorder that arises as a result of the interaction of psychological, social, technological and physiological factors and is characterized by an obsessive desire to be inseparable from a mobile device or a means of communication, or to be far from it and causes mental discomfort, feelings of fear and anxiety and disrupts the normal life process of an individual. It arises due to constant dependence on the smartphone, the fear of being unreachable and losing contact with the social environment. Fabing, mind scrolling, and nomophobia are concepts that are related because of their common roots in the overuse of digital technologies and mobile devices. They affect social interactions, mental health and overall quality of life. Understanding these connections will help to develop effective strategies for the prevention and reduction of the negative impact of these phenomena on people and society.